BCT 2022
DOI: 10.56632/bct.2022.1103
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Challenges of Social Media ‎Users: Management Students' Perspectives in ‎Two Asian Countries

Abstract: The primary objective of this study is to discover the challenges faced by social media users. To this end, the researchers first designed a scale and then asked 272 individuals from Indonesia and Oman to take it. Frequency, percentile distribution, and weighted mean were used to analyze the data qualitatively. The findings reveal that the respondents in two countries spent five hours on their social media, and with its use, they got more than one hundred online friends. Facebook and YouTube were found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Appropriate teaching methodologies and senses and emotions in teaching are of utmost importance in classroom activities and learner-teacher interactions. What the modern era has made available to us in the form of information dissemination is not reflected in our previous experiences (Bocar & Joscon, 2022). It must be noted that presenting a single method for teaching all individuals is impossible.…”
Section: Emo-sensory Educationmentioning
confidence: 91%
“…Appropriate teaching methodologies and senses and emotions in teaching are of utmost importance in classroom activities and learner-teacher interactions. What the modern era has made available to us in the form of information dissemination is not reflected in our previous experiences (Bocar & Joscon, 2022). It must be noted that presenting a single method for teaching all individuals is impossible.…”
Section: Emo-sensory Educationmentioning
confidence: 91%
“…The whole data collection process was done via the sky room platform as these kinds of social media platforms provide the users with the opportunity to access a variety of information easily and with few expenses (Bocar & Jocson, 2022). To collect the data, during the pretest, the participants were asked to watch six pre-recorded request speech act video prompts in the virtual class run on the sky room platform and respond to each video separately.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Some respondents from Indonesia felt more of a positive impact of social media than the Omani respondents. The Omani respondents of a study revealed that their sleeping patterns are negatively affected while missing the positive experiences and emotions that someone else is getting is the indicator the Indonesian respondents consider as having the highest negative effect on them (Bocar & Jocson, 2022).…”
Section: Digital Citizenship Benefitsmentioning
confidence: 99%